A multicenter study of the prevalence and risk factors of malaria and anemia among pregnant women at first antenatal care visit in Ghana - Fondjo, Linda Ahenkorah (PLoS One, 2020)
BACKGROUND: Malaria in pregnancy remains a major public health problem in Africa and Ghana and has been associated with a variety of pregnancy-related adverse complications. The development of effective and timely health policies for the prevention and control of malaria and anemia in pregnancy; requires current and consistent data on the prevalence and risk factors. We report the prevalence and risk factors of malaria and anemia from three major hospitals across three regions in Ghana. METHODS: This multicenter cross-sectional study comprising a total of 628 pregnant women was conducted at the antenatal care units of the Achimota Hospital in the Greater Accra Region (n = 199), St. Michael’s Hospital in the Ashanti Region (n = 221), and Effia Nkwanta Regional Hospital in the Western Region (n = 211). Questionnaires were administered to obtain socio-demographic, obstetrics and clinical data. Venous blood, stool and urine samples were collected for hematological profile and parasite identification using microscopy. Risk factors were evaluated using logistic regression models. RESULTS: The overall prevalence of P. falciparum malaria was 8.9%. Factors independently associated with malaria were self-reported mosquito exposure (moderate exposure: aOR = 3.11, 95% CI (1.12–8.61) and severe exposure: aOR = 10.46, 95% CI (3.86–28.34)) and non-use mosquito repellents (aOR = 3.29, 95% CI (1.70–6.39)). Multiparty (parity of 2: aOR = 0.19, 95% CI (0.05–0.70) and parity ≥3: aOR = 0.11, 95% CI (0.03–0.45)) and age (20–30 years old: aOR = 0.22, 95% CI (0.09–0.56)) reduced the odds of infection. The overall prevalence of anemia was 42.4%. The prevalence of mild, moderate and severe anemia were 35.7%, 6.1% and 0.6%, respectively. The use of water other than purified water (tap water: aOR = 3.05, 95% CI (2.06–4.51) and well water: aOR = 2.45, 95% CI (1.35–4.44)), increasing gestational age (second trimester: aOR = 2.05, 95% CI (1.41–2.97) and third trimester: aOR = 7.20, 95% CI (3.06–16.92)) and malaria (aOR = 2.40, 95% CI (1.27–4.53)) were independent risk factors for anemia. CONCLUSIONS: Although the prevalence of malaria is relatively low, that of anemia remains high. We recommend increasing efforts to make ITNs more available to strengthen malaria prevention. Public health education programs could help improve uptake and proper use of ITNs. To help reduce anemia in pregnancy, women should be empowered economically and interventions that reduce malnutrition should be encouraged. Women should be educated on early initiation of antenatal care to enhance surveillance, identification and treatment of anemia.